International joint venture partner selection: The role of the host-country legal environment - Roy, Jean-Paul; Oliver, Christine (Journal of International Business Studies, 2009)
This study attempts to enhance our understanding of how a host country's legal environment influences international joint venture (IJV) partner selection criteria. Empirical results based on survey data collected on 169 IJVs revealed that host-country rule of law perceptions negatively influence appropriation and coordination cost concerns, which positively influence partner-related criteria. Furthermore, these concerns mediate the relationship between perceptions of host-country rule of law and partner-related criteria.